Body evidence: intimate violence against South Asian women in America - Dasgupta, Shamita Das (Rutgers University Press, 2007)
Introduction / Shamita Das Dasgupta -- Understanding South Asian immigrant women's experiences of violence / Anitha Venkatramani-Kothari -- The many faces of domestic violence in the South Asian American Muslim community / Ruksana Ayyub -- Minority within a minority : reflecting on marital violence in the Nepali American community / Bidya Ranjeet and Bandana Purkayastha -- "Virginity is everything" : sexuality in the context of intimate partner violence in the South Asian community / Sandeep Hunjan and Shelagh Towson -- The aftermath of September 11 : an anti-domestic violence perspective / Maunica Sthanki -- Mental and emotional wounds of domestic violence in South Asian women / Diya Kallivayalil -- Fragmented self : violence and body image among South Asian American women / V.G. Julie Rajan -- Silences that prevail when the perpetrators are our own / Grace Poore -- The violence that dares not speak its name : invisibility in the lives of lesbian and bisexual South Asian American women / Prajna Paramita Choudhury -- The trap of multiculturalism : battered South Asian women and health care / Sunita Puri -- Ahimsa and the contextual realities of woman abuse in the Jain community / Shamita Das Dasgupta and Shashi Jain -- A communicative perspective on assisting battered Asian Indian immigrant women / Mandeep Grewal -- Law's culture and cultural difference / Sharmila Rudrappa -- Middle class, documented, and helpless : the H-4 visa bind / Shivali Shah -- Battered South Asian women in U.S. courts / Shamita Das Dasgupta -- Navigating gender, immigration, and domestic violence : advocacy with work visa holders / Rupaleem Bhuyan -- Local and global undivided : transnational exploitation and violence against South Asian women / Sujatha Anbuselvi Jesudason -- From Dhaka to Cincinnati : tracing the trajectory of a transnational violence against women campaign / Elora Halim Chowdhury